PERKEMBANGAN KETRAMPILAN BERKESIAN SEBAGAI DAYA TARIK WISATA DESA GANDU TEMANGGUNG - Jaka Riyanto (Institut Seni Indonesia Surakarta, 2020)
The potential of art and culture in the village of Gandu is very diverse, including musical groups. In an effort to improve the skills of the participants, training was held not only for gamelan music in general but also gamelan which was specifically used to accompany puppet shows. In this musical puppetry training given material in the form of musical concerts to adjust to the development of puppetry at this time. The methods used in the training include lectures, appreciation, and demonstrations. After attending the training, the participants in the karawitan group were able to demonstrate their karawitan pakeliran well and smoothly.Keywords: karawitan puppetry, Gandu village, training.